Parenterally Administered Norovirus GII.4 Virus-Like Particle Vaccine Formulated with Aluminum Hydroxide or Monophosphoryl Lipid A Adjuvants Induces Systemic but Not Mucosal Immune Responses in Mice - Suvi Heinimäki; Maria Malm; Timo Vesikari; Vesna Blazevic (Journal of Immunology Research)
Norovirus (NoV) is a main cause of acute gastroenteritis across all ages worldwide. NoV vaccine candidates currently in clinical trials are based on noninfectious highly immunogenic virus-like particles (VLPs) delivered intramuscularly (IM). Since NoV is an enteric pathogen, it is likely that mucosal immunity has a significant role in protection from infection in the intestine. Due to the fact that IM delivery of NoV VLPs does not generate mucosal immunity, we investigated whether NoV genotype GII.4 VLPs coadministered with aluminum hydroxide (Al(OH)3) or monophosphoryl lipid A (MPLA) would induce mucosal antibodies in mice. Systemic as well as mucosal IgG and IgA antibodies in serum and intestinal and nasal secretions were measured. As expected, strong serum IgG, IgG1, and IgG2a antibodies as well as a dose sparing effect were induced by both Al(OH)3 and MPLA, but no mucosal IgA antibodies were detected. In contrast, IN immunization with GII.4 VLPs without an adjuvant induced systemic as well as mucosal IgA antibody response. These results indicate that mucosal delivery of NoV VLPs is needed for induction of mucosal responses.